Bruch´s membrane thickness in relationship to axial length - Bai, Hai Xia; Jonas, Jost B. (PLOS ONE, 2017)
Purpose To assess a potential role of Bruch´s membrane (BM) in the biomechanics of the eye, we measured its thickness and the density of retinal pigment epithelium (RPE) cells in various ocular regions in eyes of varying axial length. Methods Human globes, enucleated because of an ocular tumor or end-stage glaucoma were prepared for histological examination. Using light microscopy, the histological slides were histomorphometrically examined applying a digitized image analysis system. Results The study included 104 eyes with a mean axial length of 27.9±3.2 mm (range:22.6mm-36.5mm). In eyes without congenital glaucoma, BM was significantly thickest (P<0.001) at the ora serrata, followed by the posterior pole, the midpoint between equator and posterior pole (MBEPP), and finally the equator. BM thickness was not significantly correlated with axial length (ora serrata: P = 0.93; equator:P = 0.31; MBEPP:P = 0.15; posterior pole:P = 0.35). RPE cell density in the pre-equatorial region (P = 0.02; regression coefficient r = -0.24) and in the retro-equatorial region (P = 0.03; r = -0.22) decreased with longer axial length, while RPE cell density at the ora serrata (P = 0.35), the MBEPP (P = 0.06; r = -0.19) and the posterior pole (P = 0.38) was not significantly correlated with axial length. Highly myopic eyes with congenital glaucoma showed a tendency towards lower BM thickness and lower RPE cell density at all locations. Conclusions BM thickness, in contrast to scleral and choroidal thickness, was independent of axial length in eyes without congenital glaucoma. In association with an axial elongation associated decrease in the RPE cell density in the midperiphery, the findings support the notion of a biomechanical role BM may play in the process of emmetropization/myopization.
Published: August 2, 2017
Gesehen am 28.06.2018